2001
DOI: 10.3201/eid0704.010430
|View full text |Cite
|
Sign up to set email alerts
|

Comparative West Nile Virus Detection in Organs of Naturally Infected American Crows (Corvus brachyrhynchos)

Abstract: Widespread deaths of American Crows (Corvus brachyrhynchos) were associated with the 1999 outbreak of West Nile (WN) virus in the New York City region. We compared six organs from 20 crow carcasses as targets for WN virus detection. Half the carcasses had at least one positive test result for WN virus infection. The brain was the most sensitive target organ; it was the only positive organ for three of the positive crows. The sensitivity of crow organs as targets for WN virus detection makes crow death useful f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 4 publications
0
44
1
Order By: Relevance
“…To date, this work has been restricted to naturally and experimentally infected American crows and experimentally infected blue jays. One study of naturally infected American crows used TaqMan reverse transcription-polymerase chain reaction (RT-PCR) and plaque assay to compare WNV titers in six different tissues and found brain tis-sue to be the most sensitive target organ (Panella et al, 2001). A second study using TaqMan RT-PCR on tissues of naturally infected American crows found kidney, and secondarily brain, to be infected most consistently (Kramer and Bernard, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To date, this work has been restricted to naturally and experimentally infected American crows and experimentally infected blue jays. One study of naturally infected American crows used TaqMan reverse transcription-polymerase chain reaction (RT-PCR) and plaque assay to compare WNV titers in six different tissues and found brain tis-sue to be the most sensitive target organ (Panella et al, 2001). A second study using TaqMan RT-PCR on tissues of naturally infected American crows found kidney, and secondarily brain, to be infected most consistently (Kramer and Bernard, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining tissue tropism of WNV in corvids and noncorvids indicated that the kidney was the most consistently infected tissue in birds, regardless of the level of infection. 20,22 The brain was the next most consistently positive tissue. 20,22 As in crows, antigen was most commonly found in the kidneys of affected squirrels.…”
mentioning
confidence: 99%
“…13,20,22 In contrast, horses tend to exhibit moderate or even severe histologic lesions in the brain and spinal cord, but very minimal WNV antigen, if any, can be detected by IHC. 5,19 Commonly nested RT-PCR is required to confirm the diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oral and cloacal swab specimens are used in many surveillance programs. 10,17 However, these swab specimens may lead to aerosolization of the virus on retrieval of the sample. Detection of virus in epithelial tissue has been done successfully using IHC and ACE formats for bovine viral diarrhea virus (BVDV).…”
mentioning
confidence: 99%